Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M158 - Peter Brandt; Anne-Cathrin Wölfl (PANGAEA, 2020)
Multibeam bathymetry raw data was recorded in the Atlantic during cruise M158 that took place between 2019-09-19 and 2019-10-26. The data was collected using the ship extquotesingles own Kongsberg EM 710. This data is part of the DAM (German Marine Research Alliance) underway research data project.